In-vivo Antipyretic Effect of Eel (Anguilla bicolor bicolor) Oil on Yeast-induced Fever on Mice - Heru Sasongko; Aulia Ayu Rahmawati; Yeni Farida; Sugiyarto Sugiyarto (UNIVERSITAS SEBELAS MARET (UNS), 2019)
Fish oil has been studied for medicinal purposes, including its antipyretic properties. Eel (Anguilla bicolor bicolor) oil, which contains vitamins and fatty acids, including Omega-3 (EPA and DHA), is also expected to have the antipyretic effect. This research aimed to examine the antipyretic activity of eel oil on white mice (Mus musculus L.). An in-vivo study was done on thirty Swiss-Webster strain males mice that previously got 20% yeast-induced fever. Six treatments were applied including normal group (untreated), a negative control group (yeast-treated), a positive control group treated with acetaminophen (1.764 mg/20 g body weight), and three groups treated with eel oil (0.048, 0.096 and 0.192 g/20 g body weight, respectively). The data was analyzed statistically using one way ANOVA then was continued with LSD post hoc test. The results showed that eel oil has significantly reduced yeast-induced hyperthermia on mice five hours after application at doses 0.096 and 0.192 g/20 g body weight. Our finding suggests that eel oil possess antipyretic properties when was applied in certain doses, and this effect is presumably attributed to its high content of fatty acid, including EPA and DHA.